2013
DOI: 10.1109/tcomm.2013.111513.120888
|View full text |Cite
|
Sign up to set email alerts
|

Link Adaptation with Untrusted Relay Assignment: Design and Performance Analysis

Abstract: In this paper, a link adaptation and untrusted relay assignment (LAURA) framework for efficient and reliable wireless cooperative communications with physical layer security is proposed. Using sharp channel codes in different transmission modes, reliability for the destination and security in the presence of untrusted relays (low probability of interception) are provided through rate and power allocation. Within this framework, several schemes are designed for highly spectrally efficient link adaptation and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…They demonstrated that if an untrusted relay is asked to relay information towards the destination, the secrecy rates achieved are higher as compared to the case when the relay is only considered as an eavesdropper. In [12] a link adaptation with untrusted relay assignment framework for cooperative communications is proposed by utilizing arbitrary number of relays for reliable information transfer while ensuring secrecy at the relays. The authors in [13] consider a two-user interference relay channel with the aim to secure the messages from either destinations, as well as the untrusted relay, without the presence of direct link between either of the users.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that if an untrusted relay is asked to relay information towards the destination, the secrecy rates achieved are higher as compared to the case when the relay is only considered as an eavesdropper. In [12] a link adaptation with untrusted relay assignment framework for cooperative communications is proposed by utilizing arbitrary number of relays for reliable information transfer while ensuring secrecy at the relays. The authors in [13] consider a two-user interference relay channel with the aim to secure the messages from either destinations, as well as the untrusted relay, without the presence of direct link between either of the users.…”
Section: Introductionmentioning
confidence: 99%
“…They analyzed the feasibility of employing untrusted relays with enough untrusted relays. The authors in [10] suggested relay assignment and link adaptation for both security and spectral-efficiency. High performance rate adaptive channel coding schemes with efficient power allocation is used to provide both reliability and security in the presence of untrusted relays.…”
Section: Introductionmentioning
confidence: 99%
“…High performance rate adaptive channel coding schemes with efficient power allocation is used to provide both reliability and security in the presence of untrusted relays. Within this framework, several schemes were proposed to achieve spectrally efficient link adaptation and relay selection [10]. Their results indicated the superiority of the proposed systems and it was found that power adaptation at the source plays an important part in improving spectral efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Several secure transmission techniques using trusted relays but at the presence of eavesdroppers are presented by Dong, Han, Petropulu, and Poor (2010) where continuous rate adaptation is utilised. Secure transmission scheme through untrusted AF relay is designed by Jeong, Kim, and Kim (2012) by beamforming for multiple input multiple output links and by Ju and Kim (2013), Sun, Zhang, Li, and Niu (2012), Yener and He (2008), Wang, Elkashlan, Huang, Tran, and Duong (2014) and Khodakarami and Lahouti (2013) for SISO links. In the works of Ju and Kim (2013), Sun et al (2012), Yener and He (2008) and Wang et al (2014), continuous link adaptation is utilised and in the work of Khodakarami and Lahouti (2013), discrete link adaptation is used.…”
Section: Introductionmentioning
confidence: 99%
“…In a relay network with diversity, as transmitter to relay link has always better SNR than transmitter to receiver link, probability of having secure communication is very low. In the works by Ju and Kim (2013), Sun et al (2012), Yener and He (2008) and Wang et al (2014), AF relay network without diversity and in the work by Khodakarami and Lahouti (2013), AF relay network with diversity is considered.…”
Section: Introductionmentioning
confidence: 99%